Preventing Bullying Among Schoolchildren: Persuasive Communication Between Teachers And Students At State Junior High School 14 In Cirebon City - Ilham Baihaqi Salman; Siti Khumayah; Aghnia Dian Lestari (Jurnal Polisci, 2026)
Bullying is a phenomenon that has garnered significant media attention, both on social media and in other mass media. Bullying cases most often target school-aged children, particularly those aged 13–15, although they also frequently occur among college students or adults; consequently, bullying is most prevalent in schools. Therefore, persuasive communication between teachers—as educators—and students is essential to prevent bullying. The purpose of this study is to identify the barriers that arise in the process of persuasive communication, to determine the efforts made by teachers to overcome these barriers, and to analyze the forms of persuasive communication used by teachers to prevent bullying in schools. This study employs a qualitative approach using the case study method to understand the persuasive communication between guidance counselors and students. The results of the study show that when teachers engage in persuasive communication, they do so using a psychological approach, carefully selecting the messages to be conveyed to students so that they are easily accepted. Students are given the opportunity to actively participate in bullying prevention because, after all, they are the key actors in preventing bullying. The conclusion of this study is that persuasive communication between teachers and students can prevent bullying or violence in schools.